The dialectics of image culture and their use on the artistic outcomes of students (Journal of the College of Basic Education, 2022)
The current research aims to employ the dialectics of image culture on student outcomesAnd measuring its impact by applying it to a sample of students, and to achieve the goal of the research, the researcher put the following zero hypothesis: There are no statistically significant differences at the level of significance (0.05) between the average scores of students of the two groups (T, Z) in the Institute of Fine Arts / Al-Kazimiya Holy in their answers The test items should perform dimensional skill. To achieve the goal of the research, the researcher followed the experimental design with partial control, and the research sample consisted of (50) students. The researcher was rewarded with variables and these variables are: the students' chronological age - the academic achievement of parents - a priori skill test, And the researcher used the statistical means, the statistical bag (SPSS) to show the results of the research. T-Test: To calculate the difference between the experimental and control groups for the skillful performance of making technical products.And Holsty's equation: To calculate the stability of the analysis form between the observer and the researcherIn the light of the results of the research, the researcher reached the following conclusions: The controversies of the image culture are effective and have a positive effect to increase the mastery of the skilled performance of the third grade students in the artistic outcomes.In the light of the results of the research, the researcher recommends the following: The necessity of emphasizing the use of male and female teachers in the method of dialectics of the image culture in preparing artistic outcomes, as this has a positive impact on mastering students' skills.